A Study of MHD Free Convection Flow Past an Infinite Inclined Plate - Husna Izzati, Osman; Nur Fatihah, Mod Omar; Vieru, Dumitru; Zulkhibri, Ismail (Akademi Baru, 2022)
In the present article, we have studied the magnetohydrodynamic (MHD) free convection flow past an infinite inclined plate. In order to explore the effects of velocity, temperature and concentration, Laplace transform technique has been used in this study. This method is adapted to accomplish the analytical solution of governing equation. The impact of various embedded parameter on concentration, velocity and temperature such as chemical reaction, magnetic parameter, radiation and inclination angle has been discussed graphically with numerical results.